Alat Pengukur Kecepatan Digital dan Lampu Indikator Nirkabel pada Jaket Pengendara Sepeda - Tri Rahajoeningroem; Rayagung Sidik Muslim (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2018)
Abstract – Bicycles has become the best solution to be able to reduce the level of congestion for the citizens of the world. Cycling is an activity carried out by someone to be able to go from place to destination and cycling has also become a hobby for some people. Even so, bicycles also experience infrastructure problems, namely bicycle lanes which are still rarely available. Some countries in the world have not fully provide special lanes for bicycle users. This causes bicycle users to use highways that are more often used by other vehicles. And it can cause accidents for bicycle users. Therefore, in the implementation of the wireless indicator lights on this jacket, the author wants to provide a better solution to overcome this problem, that is by combining indicator lights with jackets so that it can function to signal to other road users. In Addition, the author also designed a digital speedometer that can later appear on the LCD screen (liquid crystal display). For this speedometer, by placing a magnetic sensor on the forks as a magnetic speed reader placed on the bicycle spokes. For indicator lights on this jacket, the input uses a touch sensor and brake levers will be attached to the front of the bike through the bluetooth master transmission system and the bluetooth slave on the jacket, so the indicator light on the jacket will light up and form the right, left or stop direction and will be displayed on the LCD with the digital speedometer.Keyword : Speedometer, Bluetooth, Bicycle, Indicator Light, Wireless